2021
DOI: 10.1371/journal.pbio.3001463
|View full text |Cite
|
Sign up to set email alerts
|

Heterophilic and homophilic cadherin interactions in intestinal intermicrovillar links are species dependent

Abstract: Enterocytes are specialized epithelial cells lining the luminal surface of the small intestine that build densely packed arrays of microvilli known as brush borders. These microvilli drive nutrient absorption and are arranged in a hexagonal pattern maintained by intermicrovillar links formed by 2 nonclassical members of the cadherin superfamily of calcium-dependent cell adhesion proteins: protocadherin-24 (PCDH24, also known as CDHR2) and the mucin-like protocadherin (CDHR5). The extracellular domains of these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 108 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…Although IMAC protocadherin adhesion properties differ across species [16], previous biochemical studies established that in humans, heterophilic complexes of CDHR2 and CDHR5 exhibit strong adhesion, CDHR2 demonstrates weak homophilic adhesion, and CDHR5 demonstrates no homophilic adhesion [11]. To further study the nature of transjunctional IMACs, we developed a cell mixing approach that enabled us to drive the formation of adhesion complexes consisting of different complements of CDHR2 and/or CDHR5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IMAC protocadherin adhesion properties differ across species [16], previous biochemical studies established that in humans, heterophilic complexes of CDHR2 and CDHR5 exhibit strong adhesion, CDHR2 demonstrates weak homophilic adhesion, and CDHR5 demonstrates no homophilic adhesion [11]. To further study the nature of transjunctional IMACs, we developed a cell mixing approach that enabled us to drive the formation of adhesion complexes consisting of different complements of CDHR2 and/or CDHR5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If so, this would offer a mechanistic explanation for the upright orientation and constrained motility that microvilli demonstrate at these sites, and potentially the long-term stabilization that enables microvillar accumulation on the apical surface in large numbers. Previous work in CACO-2 BBE cells, native mouse intestinal tissue, and X-ray crystallography all indicate that the interacting ectodomains of CDHR2 and CDHR5 are structurally capable of spanning gaps up to 63 nm wide [11, 16], suggesting that they could easily reach across the ∼15 nm tight junction between neighboring cells [37]. Indeed, in the current study, super-resolution imaging revealed that CDHR2 and CDHR5 span the intercellular space to form transjunctional IMACs that physically link marginal microvilli that extend from neighboring cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging structural view of inner ear tip-links is that they are formed by a 2:2 complex of CDH23 and PCDH15, in which a cis -homodimer of CDH23 forms the upper portion of the tip-link and a PCDH15 cis -homodimer forms the lower portion (42-44). Sequence and structural analyses suggest that CDHR5 found in intermicrovillar adhesion links represents the ‘functional equivalent’ of PCDH15 found in inner ear tip-links (45). Detailed structural and biophysical studies showed that PCDH15 dimerizes by forming a double-helical assembly of two molecules, mediated by two independent cis -dimerization interfaces involving the EC2-EC3 domain region and a unique membrane-adjacent domain (MAD)(43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In microvilli, cadherin-related family member 2 (CDHR2, also known as protocadherin-24) from one microvillus interacts with a cadherin-related family member 5 (CDHR5, also called mucin-like protocadherin) from the neighboring microvillus in a head-to-head manner to form the intermicrovillar link. 13,14 Similarly, in stereocilia, the tip link is formed by cadherin-23 (CDH23, encoded by USH1D) from the taller row and protocadherin-15 (PCDH15, encoded by USH1F) from the shorter row. 15,16 The molecular components at the cytoplasmic side of these two protrusions are also similar.…”
Section: Introductionmentioning
confidence: 99%